An exploration of bullying in school context with specific focus on cyberbullying as a form of cybercrime in Tshwane, Gauteng - Preez, Cara du (Acta criminologica, 2017)
Young persons are exposed to the danger of bullying and cyberbullying as a result of the increased use of the Internet and technology. Very little research has been done about the nature and extent of cyberbullying in South Africa. This article, therefore, conceptualises the meaning of the construct of cyberbullying and explores cyberbullying in school context, as a form of cybercrime in Tshwane, Gauteng. A structured questionnaire was group administered to a non-random sample of 149 learners from four secondary (high) schools in Gauteng who agreed to participate in the research and successfully completed the questionnaires. The goal of the study was to collect and analyse data according to the gender of the participants to determine the nature, extent and prevalence of bullying compared to cyberbullying among participants in schools in Tshwane, Gauteng. Although male participants experienced less victimisation as a result of cyberbullying than their female counterparts, they were more frequently perpetrators of both traditional and cyberbullying and more frequently victims of traditional bullying which confirms that males are more inclined to be victims of traditional bullying than females. Because males turn out to be greater perpetrators of bullying, it is not strange that conventional bullying is still the most prevalent form of bullying committed by the research participants. However, substantial numbers of female respondents were involved in traditional bullying as either victims or perpetrators. Though the risk of direct physical violence is improbable, cyberbullying has serious consequences to victims thereof; especially females. This article adds to the existing volume of literature on the phenomenon of bullying with specific focus on cyberbullying, the risks and dangers involved, and how victims respond to it. Furthermore, it was to gain an understanding of the consequences of cyberbullying and reactive strategies applied to resolve it, in order to make a contribution to this under researched field of study.